PENGARUH MOTIVASI TERHADAP PENINGKATAN SEMANGAT KERJA KARYAWAN PADA CV.BERKAH HAFIZOH PALEMBANG - Mustika Ratu; Siska Fratiwi; Martini Martini (Jurnal Manajemen, 2021)
The purpose of this study was to determine how the company's efforts CV. Berah Hafizoh Palembang in improving the provision of incentives then To find out the company's efforts CV. Berah Hafizoh Palembang in providing work facilities that can affect employee morale and To find out the company's efforts CV. Berah Hafizoh Palembang in providing facilities work that can affect employee morale Research was conducted on the employees of CV. Berah Hafizoh Palembang with 50 respondents. Research respondents are all employees except the leadership level. Data collection was carried out by distributing questionnaires using a Likert scale. The data analysis technique used is the SPSS program. The results of this study reveal that motivation will affect the morale of the employees of CV. Berkah Hafizoh Palembang.